2013
DOI: 10.5581/1516-8484.20130011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iron overload on interleukin-10 levels, biochemical parameters and oxidative stress in patients with sickle cell anemia

Abstract: ObjectiveThe aim of this study was to evaluate the impact of iron overload on the profile of interleukin-10 levels, biochemical parameters and oxidative stress in sickle cell anemia patients. MethodsA cross-sectional study was performed of 30 patients with molecular diagnosis of sickle cell anemia. Patients were stratified into two groups, according to the presence of iron overload: Iron overload (n = 15) and Non-iron overload (n = 15). Biochemical analyses were performed utilizing the Wiener CM 200 automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…A human study reported that IL-10 supplementation is associated with increased risks of hyperferritinemia and anemia in Crohn’s disease patients [ 27 ]. On the other hand, sickle cell anemia patients with iron overload, defined by elevated serum ferritin of >2247 pmol/L, had lower serum IL-10 levels compared to non-iron-overloaded patients [ 28 ]. Future studies investigating the interactive effects of IL-10 and serum ferritin on testosterone are needed in order to understand how a shift in the anti-/proinflammatory balance contributes to testosterone levels in boys and adult men.…”
Section: Discussionmentioning
confidence: 99%
“…A human study reported that IL-10 supplementation is associated with increased risks of hyperferritinemia and anemia in Crohn’s disease patients [ 27 ]. On the other hand, sickle cell anemia patients with iron overload, defined by elevated serum ferritin of >2247 pmol/L, had lower serum IL-10 levels compared to non-iron-overloaded patients [ 28 ]. Future studies investigating the interactive effects of IL-10 and serum ferritin on testosterone are needed in order to understand how a shift in the anti-/proinflammatory balance contributes to testosterone levels in boys and adult men.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that, in rats receiving toxic doses of iron, the elevation of hepcidin expression in the liver was accompanied concomitantly by a significant increase of serum uric acid levels [Toledano et al, ]. It has been shown that in patients with iron overload, urea and ferritin, a protein that stores iron in the cell, levels correlated positively with uric acid levels [Barbosa et al, ]. Although iron is essential for human life, free iron in excess can have deleterious effects by catalyzing the Fenton reaction (ferrous ion‐mediated decomposition of hydrogen peroxide) and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is an anti-inflammatory cytokine whose main effect is inhibition of the synthesis of various cytokines, such as TNF-α, GM-CSF, IL-1, IL-6, IL-8 and IL-12, to promote the uptake and retention of iron within monocytes and the reticuloendothelial system. IL-10 also inhibits the proliferation of TH1 cells, decreasing cytolytic function and the secretion of TH1 cytokines and facilitating the development of a TH2 response [57].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%